The farnesyltransferase inhibitors tipifarnib and lonafarnib inhibit cytokines secretion in a cellular model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; De Leo, Luigina; Decorti, Giuliana; Crovella, Sergio; Tommasini, Alberto; Pontillo, Alessandra (Pediatr Res, 2011)
The shortage of geranylgeranyl-pyrophosphate (GGPP) was associated to an increased IL-1β release in the autoinflammatory syndrome mevalonate kinase deficiency (MKD), a rare inherited disease that has no specific therapy. Farnesyltransferase inhibitors (FTIs) act at the end of mevalonate pathway. Two FTIs, tipifarnib (Tip) and lonafarnib (Lon), were therefore evaluated as possible therapeutical choices for the treatment of MKD. FTIs could lead to a redirection of the limited available number of mevalonate intermediates preferentially to GGPP synthesis, eventually preventing the uncontrolled inflammatory response. The effect of Tip and Lon on intracellular cholesterol level (ICL) and on proinflammatory cytokines secretion was evaluated in a cellular model of MKD, chemically obtained treating RAW 264.7 cells with lovastatin (Lova) and alendronate (Ald). The combination of FTIs with the isoprenoid geraniol (GOH) was also tested both in this model and in monocytes isolated from MKD patients. Tip and Lon proved to revert the ICL lowering and to significantly reduce the lipopolysaccharide-induced cytokines secretion in Ald-Lova -RAW 264.7 cells. This anti-inflammatory effect was amplified combining the use of GOH with FTIs. The effect of GOH and Tip was successfully replicated in MKD patients' monocytes. Tip and Lon showed a dramatic anti-inflammatory effect in monocytes where mevalonate pathway was chemically or genetically impaired.
Keywords: Alendronate; Animals; Anti-Inflammatory Agents; Cell Line; Child; Child, Preschool; Cholesterol; Cytokines; Dose-Response Relationship, Drug; Enzyme Inhibitors; Farnesyltranstransferase; Humans; Inflammation Mediators; Lovastatin; Male; Mevalonate Kinase Deficiency; Mice; Monocytes; Phosphotransferases (Alcohol Group Acceptor); Piperidines; Polyenes; Polyisoprenyl Phosphates; Polyunsaturated Alkamides; Pyridines; Quinolones; Terpenes